A simple change - Miller, Judith, 1944- (Miller, Judith, 1944- Home to Amana., 2013)
"When unforeseen circumstances drive Jancey Rhoder to move to the Amana Colonies, she'll be forced to reconsider everything she wanted out of life--and love"--Provided by publisher.